Effect of social development in reducing tuberculosis mortality In northeastern Brazil areas - Ana Angélica Rêgo Queiroz; Thaís Zamboni Berra; Alexandre Tadashi Inomata Bruce; Maria Concebida da Cunha Garcia; Danielle Talita dos Santos; Marcos Augusto Moraes Arcoverde; Luana Seles Alves; Mellina Yamamura; Tereza Cristina Scatena Villa; Pedro Fredemir Palha; Francisco Chiaravalloti-Neto; Ricardo Alexandre Arcêncio (Journal of Infection in Developing Countries)
Introduction: Tuberculosis (TB) is the primary cause of death among infectious diseases affecting groups in extreme poverty. Social improvements could reverse this situation in Brazil. This study aims to demonstrate the spatial relationship between social development (SD) and TB mortality in Natal, a city in northeastern Brazil.